Reduced growth velocity at term is associated with adverse neonatal outcomes in non-small for gestational age infants. (September 2019) - Bligh, Larissa N.; Flatley, Christopher J.; Kumar, Sailesh
Abstract: Objectives: To investigate the association between decreased growth velocity at term, measured by estimated fetal weight z-score change, and adverse neonatal outcome and operative birth for intrapartum fetal compromise in a cohort of non-small for gestational age infants. Study design: A prospective observational study was conducted at Mater Mothers' Hospital, Brisbane, Australia. Serial ultrasound assessment was undertaken every two weeks from 36 weeks gestation until delivery to determine estimated fetal weight on 436 women with uncomplicated pregnancies. Intrapartum and neonatal outcomes were recorded. The outcome measures were adverse neonatal outcome [severe acidosis (cord pH < 7.0, base deficit ≤-12 mmol/L and/or lactate >6 mmol/L), low Apgar score (<7 at 5 min) or neonatal intensive care unit admission] and operative delivery for intrapartum fetal compromise. Estimated fetal weight z-score change was compared between those with and without adverse neonatal outcome and operative delivery for intrapartum fetal compromise using Generalised Linear Mixed Models. Results: The estimated fetal weight z-score per week declined for infants with the adverse neonatal outcome whilst those without demonstrated an increase [-0.04 (0.18) vs. 0.02 (0.21), p = 0.02]. There was no difference in estimated fetal weight z-score change per week in those with and without operative delivery for intrapartum fetal compromise. Conclusion: Reduced growth velocity in non-small for gestational age fetuses at term is associated with an increased risk of adverse neonatal outcomes.